STRATEGI PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DI HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON - Henderina Lelloltery; Jopie Christian Hitipeuw; Mersiana Sahureka (Jurnal Hutan Tropis, 2020)
The study aims to determine the strategy of developing ecotourism based on community participation and stakeholder involvement. The research method used was a survey method by making direct observations to the location of attractions and conducting an inventory of forms of community involvement with interview technique. Then a focus Group Disscusion (FGD) is conducted to get the same perception between the community and stakeholders. Data were analyzed qualitativelvy using SWOT analysis. The results showed that the ecotourism potential in the village of Hukurila was very diverse both in terrestrial and aquatic ecosystems including naturan and cultural potentials.The potential of natural tourism consists of Tihulessy  beach, Wailirang beach, Zeu beach, underwater cave with a variety of  coral reefs, waterfalls, beautiful landscape. Cultural potential consists of the “cuci desa ”,  cakalele dance, nyainyai dae dance, ”batu badiri’ and local wisdom ”sasi”.  Community perception shows that 83.3% of respondents agreed to develop ecotourism activities and community participation related to tourism activity planning, implementation of activities and development of tourism facilities supported by tourism stakeholders such as local governments and NGOs: IFAD, Mahina Arika and Walang Perempuan who are actively support tourism activities SWOT analysis shows ecotourism activites in Hukurila village according to quadran I (Aggressive Strategi). This position thinks about how to deal with challenges, but still has strength from an internal perspective.